Carbon sequestration for different management alternatives in sweet chestnut coppice in northern Spain. (1st November 2016) - Prada, Marta; Bravo, Felipe; Berdasco, Lorena; Canga, Elena; Martínez-Alonso, Celia
Abstract: This paper provides an innovative approach to assessing carbon sequestration in sweet chestnut coppice taking into account the importance of carbon fluxes in the whole forest-industry value chain in the mitigation of climate change. The goals of this study were: to evaluate the baseline carbon capture of sweet chestnut forest in the north of Spain; to assess the effect of thinning and extending the rotation period on carbon storage; and to evaluate the substitution effect of using sweet chestnut products as an alternative to other materials. The CO2FIX model was used to estimate carbon content in different forest components: aboveground and belowground biomass, soil and wood products, under five different thinning and rotation scenarios. Model parameterization as a function of stand age was carried out using growth data, climate data, litterfall rates, sawmill processing data, and data on the lifespan of products and their final end. Sawmill efficiency was measured in situ using the Lumber Recovery Factor. The scenarios in which only one thinning was made resulted in more total carbon accumulating than the baseline, especially when the 40 years rotation was increased by 20 years. In contrast, scenarios involving two thinning did not even reach the baseline value of total carbon. Additionally, a positive impact on GHG emissions was found for using wood to substitute other materials, i.e. cement and fossil fuel. Taken together, these results highlight the sustainability of thinning and rotation treatments in terms of carbon storage in sweet chestnut coppice, and quantifiably supports the environmental benefits of the substitution effect of sweet chestnut wood products. As such, it provides valuable information for forest managers and policy makers who wish to address climate change mitigation in forest management planning. Highlights: Establishment of the baseline of carbon capture in sweet chestnut coppice. Assessment of the effect of thinnings intensities and rotation lengths on carbon storage. Simulation of different silvicultural management alternatives (scenarios). Evaluation of the substitution effect of sweet chestnut products against alternative materials.